A triple layer printed blue OLED with blurred interface. (23rd June 2021) - Yu, Fan; Wang, Yan; Xia, Rongrong; Jian, Yihua; Liu, Lei; Chu, Tao; Wang, Zixing; Liu, Zugang; Zhang, DongYu; Cui, Zheng
Abstract: Multilayer printing is a method for producing large area organic light-emitting diode (OLED) devices with many advantages including not using shadow mask, high material utilization and low production cost. However, the issue of the dissolution of the underneath layer at the interface when depositing an upper layer, makes it difficult to fabricate a multilayer printed device. A concept of a 'blurred interface' had been proposal previously and demonstrated in multilayer-printed orange and yellow-green OLED devices. In this paper, the blurred interface concept is employed for fabricating multilayer blue OLEDs and successfully demonstrated in both double layers or triple layers printed devices. With optimized ink formulation and printing parameters settings, uniform and stable blue multilayer printed OLEDs have been fabricated.